PENGARUH BUDAYA ORGANISASI MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PALM SPRINGS GOLF COUNTRY CLUB - Maharani, Sari; Suhardi, Suhardi (Aksara Public, 2020)
The problem in this research is the possibility of applying culture in the Palm Springs Golf Country Club that hasn’t gone well with the low motivation and culture of workers to obey the rules that apply to work. This has an impact on the work that is less than the maximum. Therefore research is carried out with the aim of studying cultural orientation, motivation, and work shifts towards employee performance. The method used descriptive analysis method applied to quantitative methods. The population is Palm Springs Golf Country Club employees with 151 sample employees. Data collection using a questionnaire instrument through the test of validity and reliability. Analyzed data using multiple linear regression to determine the relationship of independent variables with the dependent variable. T Test results produce a significant value for the variable Organizational Culture by 0,00, for the Motivation variable by 0,179 and for the Work Discipline variable by 0,00. So, partially Organizational Culture and Work Discipline have a significant and positive on employee performance, Motivation has no influence on employee performance. F test results have a significant value of 0.00 with Organizational Culture, Motivation and Work Discipline have a significant and positive on employee performance.